Suppression of Interferon-α Treatment Response by Host Negative Factors in Hepatitis B Virus Infection - Wang, Jiayi; Du, Lingyao; Tang, Hong (Frontiers in Medicine, 2021)
Chronic hepatitis B virus (CHB) infection remains a major global public health issue for which there is still lacking effective curative treatment. Interferon-α (IFN-α) and its pegylated form have been approved as an anti-HBV drug with the advantage of antiviral activity and host immunity against HBV infection enhancement, however, IFN-α treatment failure in CHB patients is a challenging obstacle with 70% of CHB patients respond poorly to exogenous IFN-α treatment. The IFN-α treatment response is negatively regulated by both viral and host factors, and the role of viral factors has been extensively illustrated, while much less attention has been paid to host negative factors. Here, we summarized evidence of host negative regulators and parameters involved in IFN-α therapy failure, review the mechanisms responsible for these effects, and discuss the possible improvement of IFN-based therapy and the rationale of combining the inhibitors of negative regulators in achieving an HBV cure.